Prevalence of Cardiovascular Disease in Patients with Type 2 Diabetes Mellitus in Iran: A Systematic Review and Meta-Analysis - Mohsen Kazeminia; Nader Salari; Masoud Mohammadi (Journal of Diabetes Research)
Background. Type 2 diabetes mellitus (DM) is the most common type of DM and accounts for 90% of the cases. One of the most important complications of type 2 DM is cardiovascular complications, which are the most common cause of mortality in patients with DM. Various studies have reported different incidence rates of cardiovascular disease in patients with type 2 DM. However, no comprehensive review of previous studies has been done. This study is aimed at determining the prevalence of cardiovascular disease in patients with type 2 diabetes mellitus in Iran with a systematic review and meta-analysis. Methods. In this review, studies were first extracted searching domestic and international databases including SID, MagIran, IranMedex, IranDoc, Cochrane, Embase, ScienceDirect, Scopus, PubMed, and Web of Science (ISI), published between 2001 and September 2019. The random effects model was adopted for the analysis, and heterogeneity of the extracted studies was investigated with the I2 index. The data collected from the extracted studies were analyzed using a comprehensive meta-analysis (Version 2) software. Results. The prevalence of cardiovascular disease in patients with type 2 DM in Iran in 17 studies with a sample size of 9656 was 37.4% (95% CI: 31.4-43.8). Based on meta-regression, there was a significant difference on the effect of year of conducting the study and sample size with the prevalence of cardiovascular disease in patients with type 2 DM in Iran (p≤0.001). Conclusion. The results of this study indicated that there was a high prevalence rate of cardiovascular disease in patients with type 2 DM in Iran. Therefore, appropriate strategies should be taken to improve this situation and trace and supervise it at all levels, providing feedback to hospitals.